'WHERE YOU PLANT THE SEED, THE TREE WILL GROW': GWYN PRITCHARD AT 70. (July 2019) - Rutherford-Johnson, Tim
Abstract: The British composer Gwyn Pritchard turned 70 in 2018. The present article offers the first substantial overview of Pritchard's life and work from his earliest public compositions of the late 1960s to some of his most recent music. His early life, training and periods of self-study are covered, as well as his time as founder-director of the Uroboros Ensemble. The second half of the article offers some insights into Pritchard's methods – particularly his use of permutating six-number series to generate pitch material – revealed in conversation with the composer and supported by unpublished pre-compositional materials.